Assessment on Contents of the Learning management System - Zurinah, Suradi; Nazatul Shima, Abdul Rani (2013)
Most assume that adult learners are not concerned with access to the LMS or even with using it in their learning and would prefer a more conventional mode of learning. However, at the Asia e University in Malaysia, most of the learners are adult learners who are actively engaged in utilizing learning materials available in the learning management system (LMS). A sample group of 145 adult learners responded to the study, demonstrating that the contents of the university’s learning management system are of quality, complete, relevant and current. In addition, the sample group was satisfied (e-satisfaction) and will keep using the LMS (e-retention) in future. Index Terms— learning management system, contents, e-learning, quality information, information completeness, information relevance, information timeliness (current), e-satisfaction, e-retention.